Binormal schrodinger system of Heisenberg ferromagnetic equation in the normal direction with Q -HATM approach - Körpınar, Talat; Demirkol, Rıdvan Cem; Körpınar, Zeliha (World Scientific, 2021)
In this paper, we first study the applications of the wave propagation flow in the normal direction, which is assumed to be the path of the propagated light radiated by Heisenberg ferromagnetic equation. Then the Coriolis phase is mainly used to demonstrate the relationship between the geometric magnetic phase and parallel transportation of the wave propagation field of the evolving light radiating in the normal orientation with Heisenberg ferromagnetic equation. Moreover, we investigate the geometric magnetic interpretation of the binormal evolution of the wave propagation field in the normal direction by considering the nonlinear fractional system with the repulsive type. Finally, we obtain numerical fractional solutions for the nonlinear fractional systems with the repulsive type by using the q-Homotopy analysis transform (q-HATM) method. © 2021 World Scientific Publishing Company.
2-s2.0-85102167591
Keywords: Binormal motion; Coriolis term; Evolution; Q -HATM method; Wave polarization vector